Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors - Criquet, S; Ferré, E; Farnet, A M; Le petit, J (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.
Keywords: biodegradation; phosphatases; phosphate; phosphomonoesterases; phosphorus transformations; Quercus ilex

Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors - Criquet, S.; Ferré, E.; Farnet, A. M.; Le petit, J. (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.
Keywords: biodegradation; phosphatases; phosphate; phosphomonoesterases; phosphorus transformations; Quercus ilex